Membangun Budaya Literasi Berbasis Kearifan Lokal dalam Mata Kuliah Menulis Puisi Mahasiswa - Suryo Ediyono; Alfiati Alfiati (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2019)
Literacy is now beginning to become a discourse in various media, both print and social media. This happened since Anies Baswedan, when he was Minister of Education and Culture, launched the School Literacy Movement (GLS). Trends in global currents and the Indonesian economy are also entering the era of the creative industry revolution, an era of revolution that relies heavily on the products of the creative industries. Creative industries can be defined as industries based on expertise, talent and creativity; such as fashion, crafts, publishing (books and print media), music, film and advertising. Literary works and creative industries are both based on talent and creativity and are equally cultural. The difference is, the process of creating literary works is more oriented to the interests of the literary (literary), while the creative industry is more oriented to the interests of the market. Local Wisdom is considered so interesting to be the main topic raised in literacy development because through learning in the classroom, students will indirectly get to know the local wisdom of each region. This paper seeks to reveal the steps that can be taken so that the culture of literacy or GLS can still go hand in hand with the development of the existing creative industries. The method used is certainly descriptive and through a qualitative approach. In conclusion, the Indonesian literacy movement still needs to be promoted, and Indonesian language learning in tertiary institutions still needs to be improved, so that people become more proficient in Indonesian and continue to love Indonesian as a means of communication, cultural imaging, and strengthening the national identity. The low ability of students in the field of poetry indicates the need to empower poetry writing for students. This article aims to illustrate how to empower the literacy culture of students writing poetry in the face of the era of the creative industry revolution.